Evaluating healthcare workers needs and empowering them during pandemics - Akintujoye, Ikeoluwa Ayomiposi (Open Science Journal, 2020)
Healthcare workers play an essential and critical role in mitigating the effect of COVID-19 pandemic on the population. In the United States, estimated confirmed cases are over 3million as of July 8, 2020. Healthcare workers have increased risk of infection and, likewise, their close contact. Healthcare workers are the frontline heroes in this battle with their families as collateral damage. During the outbreak, healthcare workers have taken drastic steps to reduce the risk of infecting their family members. Some have moved out of their homes, staying in hotels, in makeshift tents in their garage, or staying with fellow healthcare workers while having decided to stay home not just because they want to get infected but mainly because they do not want to infect their loved ones and families. This paper explains how to encourage health workers to work during a disease outbreak, such as the current coronavirus called COVID-19. It is an eye-opener to what the Government can do to keep health workers encouraged to continue to render services by providing the necessary medical equipment, disposable and non-disposable gears, continuous education on proper hand hygiene, and regular check on the stockpile. The suggestion is for health workers to shower and change into a different cloth when going back home at the end of every shift, and the clothes wore at work will be recycled at the disinfecting unit within the hospital. The hospital should provide scrub that can be recycled. It will reduce the rate at which infection spread out of the hospital. Keywords: Coronavirus, COVID-19, disinfecting, and recycling work outfit, healthcare workers.